2019
DOI: 10.1186/s40425-019-0574-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the emerging role of the microbiome in cancer immunotherapy

Abstract: The activity of the commensal microbiota significantly impacts human health and has been linked to the development of many diseases, including cancer. Gnotobiotic animal models have shown that the microbiota has many effects on host physiology, including on the development and regulation of immune responses. More recently, evidence has indicated that the microbiota can more specifically influence the outcome of cancer immunotherapy. Therapeutic interventions to optimize microbiota composition to improve immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
187
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(210 citation statements)
references
References 132 publications
2
187
0
6
Order By: Relevance
“…Although it has been demonstrated that GF mice have a similar level of B and T cells, conventional and CD103 + DCs and pDCs compared to normal mice [36,39], the lack of microbiota interferes with the correct development of the immune system [36,37]. Therefore, in these mice the immune system is quite immature, and the introduction of bacteria may induce an immune response that it is not superimposable with a "physiologic" inflammatory response [40,41]. Alterations in the immune response in these mice are also testified by the fact that they do not respond to different types of immunotherapy [42,43].…”
Section: Evidences Of the Essential Role Of Lung Microbiota In Pulmonmentioning
confidence: 99%
“…Although it has been demonstrated that GF mice have a similar level of B and T cells, conventional and CD103 + DCs and pDCs compared to normal mice [36,39], the lack of microbiota interferes with the correct development of the immune system [36,37]. Therefore, in these mice the immune system is quite immature, and the introduction of bacteria may induce an immune response that it is not superimposable with a "physiologic" inflammatory response [40,41]. Alterations in the immune response in these mice are also testified by the fact that they do not respond to different types of immunotherapy [42,43].…”
Section: Evidences Of the Essential Role Of Lung Microbiota In Pulmonmentioning
confidence: 99%
“…Furthermore, additional biomarkers are under investigations such as microsatellites [5], interferon signatures [6], T cell repertoire [7], major histocompatibility complex (MHC) status [8], and immune infiltrates [9]. In the context of multiple available biomarkers the changes occurring in the microbiota composition and metabolism have been proposed as a mechanism potentially affecting the response and the toxicity to immunotherapy [10].…”
mentioning
confidence: 99%
“…The microbiome is a well-known driver of inflammation and immune response. There is a body of evidence that gut microbiota impacts the outcomes of ICB treatment in melanoma patients [105][106][107][108][109][110], leading to increasing interest in therapeutic interventions into individual microbiome composition [105,109]. Furthermore, microbiota located at the site of the lesion seems to affect the history of the disease in resected pancreatic adenocarcinoma [111].…”
Section: Other Unexplored Mechanismsmentioning
confidence: 99%